Ballad of the Bullet: Gangs, Drill Music, and the Power of Online Infamy - Stuart, Forrest (Princeton University Press, 2020)
Frontmatter -- Contents -- Preface -- Introduction -- 1. From the Drug Economy to the Attention Economy -- 2. Algorithms, Analytics, and AK-47s -- 3. Keepin’ It Real -- 4. Cashing In on Clout -- 5. When Keepin’ It Real Goes Wrong -- 6. Digital Slumming -- 7. Hometown Heroes or Local Menace? -- Conclusion -- Author’s Note -- Acknowledgments -- Notes -- References -- Index